Anatomy of the hepatic artery. Aspects of interest in liver transplantation. - Andreoli, Gustavo; Nozar, Fernando; Bado, Joaquín; Maine, Luis; Muniz, Gustavo (Cirugía del Uruguay, 2001)
Eighty-six hepatic arteries of adult cadavers were dissected for the purpose of evaluating those aspects of their anatomy which are ot interest to hepatic transplant surgery. The data consigned was: number, origin, path, topography and extremity of liver arterial pedicle(s), as well as calibre and distance to hepatic hilus of each of the potential anastomotic sites utillsed in implant